Enterprise Growth in Rural Tanzania: Comparative Analysis between Kilolo and Iringa Districts Voluntary Financial Saving Groups - Annastazia Majenga; Judith Namabira; Edson Justine (International Journal of Management, Accounting and Economics)
This study performed comparative analysis of enterprise growth among enterprises owned by members of voluntary financial saving groups (VFSGs) between Kilolo and Iringa districts in rural Tanzania. A sample of 262 members of VFSGs owning enterprises were selected proportionately from various strata. Semi-structured questionnaire was developed and used in collecting quantitative data, in-depth interview and focus group discussions were applied in collecting qualitative data. Analysis of qualitative data was carried out using content analysis. Chi-square was performed to establish association among variables under the study. Further, independent samples t-test was performed for comparative analysis of enterprise growth among enterprises owned by members of VFSGs between Kilolo and Iringa districts. The findings on association among variables were statistically significant (p < 0.05) with size of the effect being small shown by correlation coefficients (Phi and Cramer’ V coefficients < 0.30). Findings from t-test on the amount of money saved, age of members of VFSGs and number of employees were statistically significant (p < 0.05). Further, the association among education level and skills gap, loan defaulting and entrepreneurial education statistically were significant (p < 0.05). Intervention programmes through training on entrepreneurial education as capacity building is recommended to be undertaken in both districts with first priority in Kilolo district.